Nurses leading volunteer support for older adults in hospital: A discussion paper. Issue 6 (December 2022) - Saunders, Rosemary; Crookes, Kate; Gullick, Karen; Gallagher, Olivia; Seaman, Karla; Scaini, Debra; Ang, Seng Giap Marcus; Bulsara, Caroline; Ewens, Beverley; Hughes, Jeff; O'Connell, Beverly; Etherton-Beer, Christopher
Abstract: Background: The ageing population has led to growing numbers of older adults in hospital. Given the increased care needs of older adult patients, hospitals are facing resource challenges to ensure patient safety and quality of care. Support from trained volunteers focussed on older adults needs, such as eating, drinking, ambulation and cognitive stimulation have been found to improve patient outcomes. Aim: This discussion paper describes a novel nurse-led model of volunteer support providing individualised supportive care for hospitalised older adults. Methods: Discussion paper. Findings: Nurses' clinical expertise, 24-hour care and leadership skills makes them ideally placed to guide support provided by volunteers to ensure patient safety and improve quality of care. This nurse-led approach to volunteer support is underpinned by an innovative volunteer support care plan. The care plan was devised based on existing literature, and in consultation with nurses, allied health professionals, consumer representatives and volunteer managers. In practice, the plan is completed for each patient by a nurse in consultation with the patient and family following admission assessments. Trained volunteers then provide support to the patient following the care plan. Discussion: The benefits, barriers and enablers of a nurse-led volunteer support program are considered in the context of organisational and professional requirements. Conclusion: A nurse-led model of volunteer support capitalises on the clinical expertise of nurses to optimise the contribution of volunteers, positively impacting on patient outcomes, satisfaction and quality of care, with potential additional benefits to staff, volunteers and hospitals.